2008
DOI: 10.1002/chem.200801053
|View full text |Cite
|
Sign up to set email alerts
|

“Chemical Ligation”: A Versatile Method for Nucleoside Modification with Boron Clusters

Abstract: A general approach to the synthesis of nucleoside conjugates containing carborane and metallocarborane complexes, based on Huisgen 1,3-dipolar cycloaddition ("chemical ligation"), is described. Boron-cluster-donors bearing terminal azide or ethynyl groups were prepared in the ring-opening reaction of dioxane-boron-cluster adducts and an azide anion or suitable alkynol-derived alcoholate nucleophile. Analogous derivatives bearing terminal sulfhydryl groups were also prepared. Nucleosides with various spacers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…3-Iron bis(dicarbollide) redox label was covalently attached to DNA probe using "click chemistry" methodology (El-Sagheer and Brown, 2010;Wojtczak et al, 2008) in the manner providing its location close to the surface of gold electrode. This is in contrast to redox active labels and formats reported till now.…”
Section: Resultsmentioning
confidence: 99%
“…3-Iron bis(dicarbollide) redox label was covalently attached to DNA probe using "click chemistry" methodology (El-Sagheer and Brown, 2010;Wojtczak et al, 2008) in the manner providing its location close to the surface of gold electrode. This is in contrast to redox active labels and formats reported till now.…”
Section: Resultsmentioning
confidence: 99%
“…Recently a general method was proposed for the synthesis of nucleoside libraries bearing carborane or metallacarborane modification for biochemical screening using Huisgen 1,3-dipolar cycloadition of azides and terminal alkynes, a ''click" chemistry approach [13]. It was found that also B 12 -based azides undergo Cu I -catalyzed ''click" reactions with various alkynes leading to corresponding triazoles in high yields [12].…”
Section: Resultsmentioning
confidence: 99%
“…11 B NMR (ppm): 6.3 (1B, s, B(1)); À16.8 (5B, d, B(2-6)); À18.2 (5B, d, B(7-11)); À22.5 (1B, d, B (12)). 13 C NMR (ppm): 163.1 (C-4); 150.8 (C-2); 135.3 (C-6); 108.9 (C-5); 87.8 (C-4 0 ); 85.2 (C-1 0 ); 71.1 (C-3 0 ); 70.7, 68.1, 66.9 (CH 2 O-spacer); 61.6 (C-5 0 ); 58.0 (NCH 2 CH 2 CH 2 CH 3 ); 41.2 (CH 2 N-spacer); 39.9 (C-2 0 ); 23.5 (NCH 2 -CH 2 CH 2 CH 3 ); 19.7 (NCH 2 CH 2 CH 2 CH 3 ); 13.9 (NCH 2 CH 2 CH 2 CH 3 ); 13.4 (5-CH 3 ).…”
Section: Synthesis Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…Compound 2 was synthesized by the modification of a described procedure. 33 A freshly prepared solution of sodium propynolate (3 mg of sodi um per 1 mL of propargyl alcohol) was added at 0 °С to a solution of compound 1 (41 mg, 0.1 mmol) in acetonitrile (10 mL), and the mixture was left for 48 h. The reaction course was monitored by TLC. Water (100 μL) was added after the end of the reaction.…”
Section: Methodsmentioning
confidence: 99%